(untitled) (Journal of Family Sciences, 2025)
Parental divorce can affect how an individual develops self-esteem and self-disclosure in themselves. This study aimed to determine the relationship between self-esteem and, self-disclosure, and fear of intimacy. This study uses a quantitative research design involving 300 participants. Participants were obtained through purposive sampling techniques with the criteria of individuals who have divorced parents and are 18-25 years old. The data were then analyzed using a multivariate analysis method using Structural Equation Modeling (SEM) with the help of the LISREL 8.80 program. The results showed that self-esteem and self-disclosure were negatively and significantly correlated with fear of intimacy. The findings of this study indicate that self-esteem and self-disclosure are important factors that play a role in the development of fear of intimacy in young adults. This study implies that interventions to increase self-esteem and self-disclosure can help reduce fear of intimacy.